Case Report And Case Series: Is There Room For Them? - Keyse Loyanne Batista da Silva; Samara Maria Douets Vasconcelos Cunha Dias; Rivadávio Fernandes Batista de Amorim (Brazilian Society of Geriatrics and Gerontology, 2024)
This article is part of a special series developed to assist authors in the process of scientific writing and communication. The purpose of the study was to underscore the importance of publishing case reports and case series in the medical and health sciences and to provide insights to guide the authors who wish to submit these types of study. A non-systematic review was conducted to present a brief historical overview on reports published in the literature and to provide data on the main difficulties faced by authors trying to publish in the current scenario and on the contributions of case reports and case series to scientific progress. Finally, we address the current paradox of the simultaneous depreciation of this type of publication and reinforcement of the importance of publishing emblematic cases with major impact on the progress of medical science.